ANALISIS KEMAMPUAN KEUANGAN DAERAH KABUPATEN NGADA SEBELUM DAN SESUDAH PEMEKARAN - Maria Fransiska Wist Towa; Abdul Halim (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2014)
This research is to analyze the local financial capability of Ngada Regency before and after the expansion by measuring and analyzing local financial capacity indicated by Fiscal Autonomy Degree (DOF), Routine Capacity Index (IKR) and PAD Performance Index (IPPAD). It is also analyze the correlation between local financial capability with the economic development of Ngada Regency. The data used in this research was secondary data in the form of time series with the observation period was from 2002 to 2011. The analysis tools to answer the research’s purpose were the indicator of local financial capability through Fiscal Autonomy Degree (DOF), Routine Capacity Index (IKR) and PAD Performance Index (IPPAD), paired samples test and pearson correlation.The research finding showed that the local financial capability of Ngada Regency was still low, where the Fiscal Autonomy Degree (DOF) was very less because the ratio is < 10 percent, Routine Capacity Index (IKR) had shortage since it is < 20 percent and the ratio of PAD Performance Index (IPPAD) was poor because IPPAD was < 1. There was a significant difference of the local financial capability between before and after the expansion of Ngada Regency showed by Fiscal Autonomy Degree (DOF). There was no correlation between the indicators of local financial capability (DOF, IKR and IPPAD) with the indicators of economic development through the indicator of GDP’s Ngada Regency.